Strategic Spatial Planning and Territorial Asymmetries. Grenoble and Greater Geneva: Two Alpine City Regions Put to the Challenge of Coherence - Nathalie Bertrand; Dominik Cremer-Schulte; Mathieu Perrin (Revue de Géographie Alpine)
Territorial coherence is today a guiding principle of spatial planning, especially at the city-region scale. The increasing number of spatial planning initiatives on such extended perimeters comes with the hope of a renewed relationship between cities, outskirts and rural areas. The aim of this article is to show that the governance processes at work in strategic spatial planning projects tend to reveal, or even to maintain, disparities between urban and peripheral areas, especially in mountain regions. Such areas’ ability to influence spatial projects proves to be uneven since they have different resources (financial, social, human and institutional). Based on spatial planning documents and interviews, the research reported in this article analyses the planning initiatives in two alpine city regions: Greater Geneva and Grenoble.